2019
DOI: 10.2478/pjct-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Study of selected physical, chemical and biological properties of selected materials intended for contact with human body

Abstract: The purpose of the conducted study was to analyse new materials intended for contact with the human body in view of their physical, chemical and biological properties. The authors have put to test six commercially available materials, four out of which were composite polyamide 12-based materials, while two were polyurethanes. The examined materials were assessed in terms of the surface. Subsequently, their hardness and biocompatibility were tested. The authors devoted major attention to the tests of absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The iron compounds contained in the halloysite (18-22%) support cell proliferation. Research performed in 2006 [31] showed an increase in HeparRG ™ (human hepatic cell line) proliferation in response to halloysite.…”
Section: Results Of Cytotoxicity Testmentioning
confidence: 99%
“…The iron compounds contained in the halloysite (18-22%) support cell proliferation. Research performed in 2006 [31] showed an increase in HeparRG ™ (human hepatic cell line) proliferation in response to halloysite.…”
Section: Results Of Cytotoxicity Testmentioning
confidence: 99%
“…Polymer composites, which include supplementary modifi ers (e.g. powder) in addition to the abovementioned fi bres, are referred to as hybrid composites [17][18][19]. They are designed primarily to improve selected properties of composites that contribute to their fi nal application character.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine the effect of the composition of the materials [ 10 , 11 ] as well as the working conditions (such as temperature, UV radiation and humidity) on the properties for parts made of these materials.…”
Section: Introductionmentioning
confidence: 99%